2006
DOI: 10.1007/bf03161183
|View full text |Cite
|
Sign up to set email alerts
|

Cardioactive steroid poisoning: A comparison of plant- and animal-derived compounds

Abstract: Introduction: Cardioactive steroids (CASs) are found in plants, animals, and insects. Their affinity for Na+-K+ ATPase is attenuated by the type of lactone at carbon 17 (C17) of the steroid backbone: those with 5-membered lactone rings, or cardenolides, are derived mostly from plants with 6-membered rings or from animals with bufadienolides. A systematic review of CAS poisoning was performed to compare the mortality rate of cardenolides and bufadienolides.Methods: MEDLINE was searched for articles using common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…They found distinct mutations in toads, suggesting that the bufadienolidebinding sites of NKA have been altered through evolution to confer resistance to cardiotonic steroids. Zhen et al (2012) reported that several independent lineages of insects that consume cardiotonic cardenolides, which are similar in chemical structure and pharmacological action to bufadienolides (Barrueto Jr et al, 2006), have evolved mutant forms of NKA that confer resistance to those toxins. A similar study by Feldman et al (2009) on tetrodotoxin (TTX)-resistant garter snakes (Thamnophis) found mutations in the genes coding for sodium channels (NA v1.4), which are the target molecules of TTX.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They found distinct mutations in toads, suggesting that the bufadienolidebinding sites of NKA have been altered through evolution to confer resistance to cardiotonic steroids. Zhen et al (2012) reported that several independent lineages of insects that consume cardiotonic cardenolides, which are similar in chemical structure and pharmacological action to bufadienolides (Barrueto Jr et al, 2006), have evolved mutant forms of NKA that confer resistance to those toxins. A similar study by Feldman et al (2009) on tetrodotoxin (TTX)-resistant garter snakes (Thamnophis) found mutations in the genes coding for sodium channels (NA v1.4), which are the target molecules of TTX.…”
Section: Discussionmentioning
confidence: 93%
“…Zhen et al . () reported that several independent lineages of insects that consume cardiotonic cardenolides, which are similar in chemical structure and pharmacological action to bufadienolides (Barrueto Jr et al ., ), have evolved mutant forms of NKA that confer resistance to those toxins. A similar study by Feldman et al .…”
Section: Discussionmentioning
confidence: 99%
“…The effective substance in the plants are ephedrine and pseudoephedrine. 63 Cardiovascular toxic manifestations of Ephedra include arrhythmias (e.g., ventricular tachycardia/fibrillation), acute myocardial infarction, vasoconstriction, hypersensitivity myocarditis, coronary artery aneurysm, thrombosis, and vasculitis. 64À67 Pathogenesis include endothelial dysfunction, stimulation of alpha and beta receptor agonist with increased secretion of catecholamines, and promoting inflammatory process.…”
Section: Treatmentmentioning
confidence: 99%
“…Ouabain belongs to a group of compounds, the cardiotonic steroids, which are composed of a steroidal backbone, the aglycone, or genin; a five-membered unsaturated lactone ring; and a sugar moiety, which varies depending on the type of cardenolide (15). Ouabain binds to the extracellular side of the Na-K-ATPase ␣-subunit, preferentially docking to the E2 phosphorylated conformation of the transporter.…”
Section: The Cardenolide Ouabainmentioning
confidence: 99%